Intracellular pH-induced fluorescence used to track nanoparticles in cells. Issue 27 (5th June 2015) - Cheng, F. R.; Chen, Y.; Su, T.; Cao, H.; Li, S.; Cao, J.; He, B.; Gu, Z. W.; Luo, X. L.
Abstract : pH-induced fluorescence conversion of spiropyran in nanoparticles was used as a probe for intracellular tracing and pH-sensitive drug release. Abstract : A nanoparticle with pH-induced fluorescence was reported for intracellular tracking. The fluorescence was evoked by the isomerization of the ring-closed form spiropyran (SP) to the ring-open form merocyanine (MC) in the weak acidic environment of cells. The SP–MC switch accelerated the dissociation of nanoparticles to trigger the release of trapped paclitaxel.